2024
DOI: 10.35848/1347-4065/ad3e57
|View full text |Cite
|
Sign up to set email alerts
|

Si-doped (AlGa)2O3 growth on a-, m- and r-plane α-Al2O3 substrates by molecular beam epitaxy

Hironori Okumura,
Andréa Fassion,
Cédric Mannequin

Abstract: We reported the growth of (AlGa)2O3 layers on (11-20), (10-10), and (10-12) α-Al2O3 substrates using molecular beam epitaxy, and the electrical characterization of Si-doped (AlGa)2O3 layers. The Ga2O3 layers grown on (10-10) and (10-12) α-Al2O3 were α-phase single crystals, while the Ga2O3 layer grown on (11-20) α-Al2O3 consisted of (11-20) α-Ga2O3 and (-201) β-Ga2O3. The Al composition of the (11-20) and (10-10) (AlGa)2O3 layers was controlled by varying the Al flux. The Si-doped (10-10) α-(Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The bandgap energy of α-(Al 0.56 Ga 0.44 ) 2 O 3 is estimated to be 6.88 eV. 34) Still, σ of the MOCVD-grown (AlGa) 2 O 3 layers were small, which we expect is likely due to the larger amount of compensating centers incorporated at the higher growth temperatures and additional alloy scattering that reduces the mobility relative to α-Ga 2 O 3 . As previously mentioned, the larger band gap alloys are more amenable to the formation of compensating acceptors like cation vacancies that can complex and incorporate with hydrogen, as well as complex with incorporated Si shallow donors (which are already favorable in the limit of no Al).…”
Section: (Alga) 2 O 3 Layersmentioning
confidence: 77%
See 3 more Smart Citations
“…The bandgap energy of α-(Al 0.56 Ga 0.44 ) 2 O 3 is estimated to be 6.88 eV. 34) Still, σ of the MOCVD-grown (AlGa) 2 O 3 layers were small, which we expect is likely due to the larger amount of compensating centers incorporated at the higher growth temperatures and additional alloy scattering that reduces the mobility relative to α-Ga 2 O 3 . As previously mentioned, the larger band gap alloys are more amenable to the formation of compensating acceptors like cation vacancies that can complex and incorporate with hydrogen, as well as complex with incorporated Si shallow donors (which are already favorable in the limit of no Al).…”
Section: (Alga) 2 O 3 Layersmentioning
confidence: 77%
“…The σ of the Si-doped (AlGa) 2 O 3 layer decreased with increasing Al composition, corresponding to the Si-doped (AlGa) 2 O 3 layers grown by mist CVD and MBE. 31,34) Previous DFT calculations have identified that the ionization energies of several shallow donors tend to increase with Al composition, as well an increased solubility of compensating acceptors like cation vacancies that become more favorable with larger band gaps and donor-doping, which both contribute to a decreased σ due to the small carrier concentration depending on the dopant choice and alloy composition. 30) For example, Sn dopants that have been previously used in the pure Ga 2 O 3 films become inactive at ∼30% Al, indicating the need for Si doping that we have pursued in this work for higher Al contents.…”
Section: (Alga) 2 O 3 Layersmentioning
confidence: 99%
See 2 more Smart Citations